An Everyday Robotic System that Maintains Local Rules Using Semantic Map Based on Long-Term Episodic Memory - Furuta, Yuki; Okada, Kei; Kakiuchi, Yohei; Inaba, Masayuki (2018 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS), 2018)
To enable robots to work on real home environments, they have to not only consider common knowledge in the global society, but also be aware of existing rules there. Since such "local rules" are not describable beforehand, robot agents must acquire them through their lives after deployment. To achieve this, we developed a framework that a) lets robots record long-term episodic memories in their deployed environments, b) autonomously builds probabilistic object localization map as structurization of logged data and c) make adapted task plans based on the map. We equipped our framework on PR2 and Fetch robots operating and recording episodic memory for 41 days with semantic common knowledge of the environment. We also conducted demonstrations in which a PR2 robot tidied up a room, showing that the robot agent can successfully plan and execute local-rule-aware home assistive tasks by using our proposed framework.